(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2024)
The aim of this study was to use the dermal denticles as taxonomic identification tools, in shark and rays species gutted and processed for human consumption. The specimens come from surveillance actions by environmental protection agencies between 2018 and 2020 in South Brazil. For the dermal denticles analyses, skin samples were extracted and submitted to protocol for Scanning Electronic Microscopy (SEM). Whenever possible, the validation of the identification was done with base on published references. The identification within the Carcharhiniformes was challenging due to similarities among denticles of the different families, but the only characteristic shared by this order was the presence of crests, which varied in shape and size. The Squaliformes, represented by S. megalops, varied considerably in shape. In the Squatiniformes the denticles were robust and oval shaped. Through the analysis of a remaining piece of skin on a muscle sample already processed for consumption, the identification to genus was possible, revealing that the individual was Squatina. This study demonstrated that dermal denticles are key tools for the taxonomic identification in absence of external morphologic characters that would lead to the direct species identification. In most cases, the identification was possible at least to genus. The identified genera were: Atlantoraja, Myliobatis, Sphyrna, Squalus and Squatina. Furthermore, it was observed that the more complex is the taxonomic identification of a taxon, such as genus Squalus, the more is the difficulty in the identification to species with the dermal denticles.